Pengaruh Penerapan Strategi Pembelajaran Scaffolding terhadap Kemampuan Pemahaman Konsep Matematis Siswa Madrasah Tsanawiyah Al-Hidayah Singingi Hilir ditinjau dari Motivasi Belajar Siswa - Saputri Indah Lestari; Lies Andriani (Suska Journal of mathematics Education, 2019)
This research was instigated by the problem in the field showing that their mathematic concept understanding ability was low at Islamic Junior High School of Al Hidayah Singingi Hilir. One of learning anternative strategy could direct to the students in increasing mathematic concept understanding ability was scoffolding learning straytegy. the research aimed at investigating whether there was or not difference mathematic concept understanding ability between students joining Scaffolding learning strategy and student joining teacher implementing based on their learning motivation at Islamic JuniorHigh School of Al Hidayah Singingi Hilir.  It was quasi experimental research with nonequivalent posttest-only control group design. Population of this research were the students at the eight grade of Islamic Junior High School of Al Hidayah Singingi Hilir. Sample of this research was used sampling purposive technique. VIII of B as experimental group was given Scaffolding learning strategy and VIII of A as the control group given teacher learning implementing.Instrument of collecting data was used decription test to measure their mathematic concept understanding and questionnaire to measure their learning motivation. Two way ANOVA was the technique of data analysis.  Based the data analysis could be concluded that         1) there was a difference student mathematic concept understanding ability joining Scaffolding learning strategy and did not joining Scaffolding learning Strategy. 2) There was no an interaction between Scaffolding learning strategy and their learning motivation toward their mathematic concept understanding abilityKeywords:  Scaffolding, Mathematic Concept Understanding Ability Student Learning, Motivation